The Relationship between the Use of Edulearning and the Learning Outcomes of PAI and Ethics in Grade VIII Junior High School Students - hilmi, fuad (Edukasi: Journal of Educational Research, 2024)
This study examines the relationship between the use of Edulearning and the learning outcomes of Islamic Religious Education (PAI) and Ethics in grade VIII students at Mekar Arum Junior High School. The background of the research is based on the increasing role of technology in education, although its implementation often faces obstacles, such as teachers' lack of understanding of technology and limited access by students. Using a qualitative approach and correlational methods, this study involved 206 students as subjects. The data shows that the average use of Edulearning is at a score of 3.8 (scale 1-5), with an average learning outcome of 78.5 (scale 0-100). The majority of students achieved the "Good" (46.6%) and "Very Good" (22.3%) learning outcome categories, indicating the effectiveness of Edulearning in supporting learning. However, this effectiveness is influenced by factors such as student motivation, access to technology, and teachers' skills in utilizing platform features. The conclusion of the study emphasizes the need to optimize Edulearning through teacher training, equitable distribution of technology facilities, and value-based learning strategies to improve academic learning achievement and student character building.